Reinterpreting environmental scarcity and conflict - Webersik, C (2005)
﻿ The thesis explores links between resources and conflict in contemporary Somalia. The central research questions were: Why did a society which is believed to be resilient and adaptive to its harsh environment become vulnerable? To what extent did environmental factors contribute to the emergence of conflict? How can natural resource scarcity and abundance be related to the existence of, or potential for, violent conflict, bearing in mind the historical, political, economic and cultural context of conflict? Can other determining factors such as power-relations, access to trade, or clan affiliation be linked to lower economic, institutional, and social performance and associated with higher levels of violent conflict? If a link can be made, this will help to forecast where conflict might take place. Because Somalia is largely an arid country, highly susceptible to natural disasters, and because its people have been victims of severe famine in recent decades, my starting point for this research was to investigate literature on the supposed environmental causes of conflict. Analysis of the literature which links environmental degradation and scarcity to state-collapse or civil war suggested, however, that such linkages are problematic. I argue instead that people engage in violent conflict in Somalia because they struggle to establish control over valuable resources. These resources are likely to be renewables, such as cash crops in the form of plantations in riverine areas, cereals in the Bay region, and charcoal in the coastal region of Brawa. Conflict arose over the struggle to monopolise these resources, and over the distribution of profits. Clan leaders sought to expand a source of 'tax' revenue by controlling trade networks, seaports and airports. This general approach may explain why southern Somalia has experienced continuous insecurity over the past decade.